Author Correction: Genetic dissection of clonal lineage relationships with hydroxytamoxifen liposomes. Issue 1 (December 2018) - Ransom, Ryan; Foster, Deshka; Salhotra, Ankit; Jones, Ruth; Marshall, Clement; Leavitt, Tripp; Murphy, Matthew; Moore, Alessandra; Blackshear, Charles; Brett, Elizabeth; Wan, Derrick; Longaker, Michael
In the original version of this Article, the authors inadvertently omitted Elizabeth A. Brett, who contributed to the generation of the histology figures, from the author list.This has now been corrected in both the PDF and HTML versions of the Article.